BRAFp.V600E, p.V600K, and p.V600R Mutations in Malignant Melanoma: Do They Also Differ in Immunohistochemical Assessment and Clinical Features?. Issue 1 (January 2016) - Ponti, Giovanni; Tomasi, Aldo; Maiorana, Antonio; Ruini, Cristel; Maccaferri, Monia; Cesinaro, Anna M.; Depenni, Roberta; Manni, Paola; Gelsomino, Fabio; Giusti, Francesca; Garagnani, Lorella; Pellacani, Giovanni
Abstract : Introduction: Although the detection of BRAF p.V600E mutation by immunohistochemistry was clearly described in melanoma, discordant evidences were reported for the detection of p.V600K and p.V600R mutations. The aim of the study was to evaluate the efficacy of BRAF p.V600E, p.V600K, and p.V600R detection by immunohistochemistry in melanoma. Materials and Methods: Immunohistochemistry with VE1 antibody was performed on 18 tissue samples of metastatic melanomas with known BRAF mutational status. Results: The concordance rate of immunohistochemistry was 100% for p.V600E mutation. In contrast, the 7 p.V600K-mutated melanomas were scored as negative. p.V600K-mutated melanomas were significantly associated with older age, male sex, and worst clinical outcome. Conclusions: Immunohistochemistry could efficaciously be adopted as a first step for the detection of BRAF p.V600E mutation in the initial selection of patients with advanced melanomas as candidates for BRAF inhibitors. It should be followed by molecular techniques in p.V600E-negative melanomas, for the specific search of p.V600K and other non-p.V600E BRAF mutations.